Gender and Age Differences in the Attitudes of Junior High School Students Towards Punishment - Dangor, Kassim File (MultiTech Publisher, 2024)
The study sought to investigate gender and age differences of Junior High School (JHS) students in the Sissala East Municipality in terms of their attitudes towards punishment. The study used the descriptive survey design to carry out the investigation. Data for the study was collected by administering a closed-ended Likert scale questionnaire to respondents with a sample size of 291. Responses were analyzed using the Mann-Whitney U test. Findings of the study show no statistically significant differences in the attitude of JHS students in the Sissala East Municipality towards punishment on the bases of both sex and age. The study concluded that gender and age have no influence in the attitude of JHS students in the Municipality towards punishment.